LANGUAGE VARIATION OF THE MAIN CHARACTER IN THE MOVIE BLACK PANTHER 2018 - Adhien Diani; Sari Rejeki; Maulana Taufik (Universitas Pakuan, 2021)
The occurrence of language variation is not only caused by homogeneous speakers but also because of diverse social interactions. This diversity will increase if the language is used by many speakers, because guidelines for social interaction is needed. This research discusses components of speech event, domain and the use of language variations of the main character in the movie Black Panther (2018). The purpose of this research is to identify the language variations used by the main character, and to show that the components of speech event which support the choice of the language variations. Using the descriptive analysis, and the proficient free listening techniques, the research yields to identify speech variations according to Martin Joss. The most frequently used of language variations by the main character is the casual style. The most scarcely language variations used are the intimate style and the consultative style. It can be proven that the component of speech event and domain strongly supports the use of the language variations.Keywords: components of events; domain; language variations; main character.